2016
DOI: 10.1096/fj.201500161
|View full text |Cite
|
Sign up to set email alerts
|

CK2 activity is required for the interaction of FGF14 with voltage‐gated sodium channels and neuronal excitability

Abstract: Recent data shows that fibroblast growth factor 14 (FGF14) binds to and controls the function of the voltage-gated sodium (Nav) channel with phenotypic outcomes on neuronal excitability. Mutations in the FGF14 gene in humans have been associated with brain disorders that are partially recapitulated in Fgf14 2/2 mice. Thus, signaling pathways that modulate the FGF14:Nav channel interaction may be important therapeutic targets. Bioluminescence-based screening of small molecule modulators of the FGF14:Nav1.6 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 50 publications
2
60
0
Order By: Relevance
“…In previous studies, we showed that FGF14 forms a complex with neuronal Nav1.6 channel, and this interaction is controlled by S/T kinases (Hsu et al, 2015, 2016; Shavkunov et al, 2013). The S226 residue of FGF14 is located in the C-terminal tail of the protein in a region enriched with other S/T sites (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In previous studies, we showed that FGF14 forms a complex with neuronal Nav1.6 channel, and this interaction is controlled by S/T kinases (Hsu et al, 2015, 2016; Shavkunov et al, 2013). The S226 residue of FGF14 is located in the C-terminal tail of the protein in a region enriched with other S/T sites (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…5A–B) (Hsu et al, 2015, 2016; Ali et al, 2016; Ali et al, 2014; Shavkunov et al, 2013; Shavkunov et al, 2012; Shavkunov et al, 2015). HEK293 cells were transiently transfected with CLuc-FGF14 and CD4-Nav1.6 -C-tail- NLuc plasmids expressing the coding sequence of FGF14 and the C-terminal tail of Nav1.6 fused to the single transmembrane domain protein CD4, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations